A Novel Protozoa Parasite-Derived Protein Adjuvant Is Effective in Immunization with Cancer Cells to Activate the Cancer-Specific Protective Immunity and Inhibit the Cancer Growth in a Murine Model of Colorectal Cancer - Rajesh Mani; Chloe G. Martin; Kanal E. Balu; Qingding Wang; Piotr Rychahou; Tadahide Izumi; B. Mark Evers; Yasuhiro Suzuki (Cells, 2024)
Cancer-specific CD8+ cytotoxic T cells play important roles in preventing cancer growth, and IFN-γ, in addition to IL-12 and type I interferon, is critical for activating CD8+ cytotoxic T cells. We recently identified the capability of the amino-terminus region of dense granule protein 6 (GRA6Nt) of Toxoplasma gondii, an intracellular protozoan parasite, to activate IFN-γ production of microglia, a tissue-resident macrophage population. Therefore, in the present study, we examined whether recombinant GRA6Nt protein (rGRA6Nt) functions as an effective adjuvant to potently activate cancer-specific protective immunity using a murine model of MC38 colorectal cancer (CRC). When mice were immunized with non-replicable (either treated with mitomycin C or irradiated by X-ray) MC38 CRC cells in combination with rGRA6Nt adjuvant and received a challenge implantation of replication-capable MC38 tumor cells, those mice markedly inhibited the growth of the implanted tumors in association with a two-fold increase in CD8+ T cell density within the tumors. In addition, CD8+ T cells of the immunized mice secreted significantly increased amounts of granzyme B, a key mediator of the cytotoxic activity of CD8+ T cells, and IFN-γ in response to MC38 CRC cells in vitro when compared to the T cells from unimmunized mice. Notably, the protective effects of the immunization were specific to MC38 CRC cells, as the immunized mice did not exhibit a significantly inhibited growth of EL4 lymphoma tumors. These results indicate that rGRA6Nt is a novel and effective protein adjuvant when used in immunizations with non-replicable cancer cells to potently activate the protective immunity specifically against the cancer cells employed in the immunization.